How does formal leadership influence a district content coaching program? - Hudson, Sarah E. (Kansas State University, 2010)
The titles of professional books on the topic of coaching are numerous, coaching professional development offerings are widespread and schools across the country are hiring teachers to serve in coaching roles. There is great interest around the topic of coaching and much is being written about the support that is needed for coaches as well. According to professional literature the few case studies that have been done address various types of coaching in different contexts—making it impossible to draw conclusions across them. While there is an abundant amount of literature around the topics of the various coaching roles and support needed for coaching, a study of the implementation of a coaching approach and the role of leadership has not been conducted. We do not know about the range of coaching experiences, how those arrangements were enacted and the formal leadership features in these partnerships. This study provides information that addresses this gap in the literature. This qualitative study used the path-goal theory of leadership and the 21 leadership responsibilities identified by the Mid-Continent Research for Education and Learning as a means to examine one school district’s approach to implementing a content coaching program. Thirty-two participants including Central Office personnel, principals, and content coaches were interviewed. The themes of this study suggest that it is important to establish goals and guidelines for a coaching program as foundational pieces. From these goals and guidelines, coaching roles and responsibilities can be clearly established and outcomes measured. In addition, the study suggests key pieces of good coaching partnerships to include support in many varieties and opportunities from strong professional development specific to coaching to networking with coaches. Further, the study identifies leadership responsibilities that impact second-order change that can contribute to these coaching partnerships. Recommendations to implementing successful content coaching programs in this study are discussed.
Keywords: Content Coaching and Leadership; Education, Administration (0514)